Blood pressure characteristics in Kabardino-Balkaria schoolchildren - L. V. El’garova; A. A. El’garov (Кардиоваскулярная терапия и профилактика, 1970)
Aim. To investigate regional blood pressure (BP) features in Kabardino-Balkaria Republic (KBR) schoolchildren, as well as to determine the number of children and adolescents with increased BP (IBP), who needs preventive intervention. Material and methods. In 1991-98, more than 6000 schoolchildren aged 7-17 years, from 5 KBR cities and 10 villages, were examined. BP levels, physical and gender maturity, total cholesterol, triglycerides, high-density lipoprotein (HDL) cholesterol levels were assessed. Data analysis was age, gender, ethnicity, and region-specific. Results. Age, gender, national, and climate-geographical features of BP levels were identified in KBR schoolchildren. Regional tables for systolic and diastolic BP (SBP, DBP) percentile distribution in children and adolescents aged 7-17 years were created. IBP and other cardiovascular risk factor prevalence, together with the need for preventive intervention, were determined. Conclusion. In KBR children, population-level prevention is needed, pediatric service should pay more attention to a serious problem of arterial hypertension.